Chitosan / nano-hydroxyapatite guided bone regeneration membrane with density composite structure and preparation method of chitosan / nano-hydroxyapatite guided bone regeneration membrane
By using chitosan and calcium nitrate dipotassium hydrogen phosphate from shrimp and crab shells, combined with freeze-drying and mechanical extrusion, a dense-spreading chitosan/nanohydroxyapatite guided bone regeneration membrane was prepared, and the solution was solved The existing problems of high cost of guiding bone regeneration membrane and insufficient bone mineralization capacity have achieved better results in the repair of cement defects.
Patent Information
- Application Number
- CN202411337502.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing guided bone regeneration membrane is costly and lacks bone mineralization capacity, resulting in poor treatment effect and it is difficult to benefit more people.
Chitosan from shrimp and crab shells is used as an organic matrix, combined with calcium nitrate and dipotassium hydrogen phosphate, and a chitosan/nanohydroxyapatite-guided bone regeneration membrane with dense and complex structure is prepared by freeze-drying and mechanical extrusion. , realize nanomechanics to enhance bone mineralization capabilities.
It reduces costs, improves bone mineralization effect, provides a better tissue regeneration environment, and is suitable for dental defect repair.
Smart Images

Figure CN119139565A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and in particular relates to a chitosan / nano-hydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure and a preparation method thereof. Background Art
[0002] The function of guided bone regeneration membrane is to act as a barrier membrane to prevent invasion from surrounding soft tissues, so that osteoblasts at the bone surface have enough time to proliferate, and finally achieve the purpose of tissue regeneration. Since the advent of guided bone regeneration membrane, various types of guided bone regeneration membranes have emerged in an endless stream, with differences in single-layer, double-layer and multi-layer structures, absorbable and non-absorbable materials, and differences in production processes such as electrospinning membrane formation. Currently, most existing guided bone regeneration membranes are derived from animal collagen, which is relatively expensive, and imported products account for a large market share, which is difficult for most people to afford. Therefore, inventing a new type of guided bone regeneration membrane to benefit more people is an urgent problem to be solved.
[0003] In order to solve the existing problems, the present invention starts with raw materials and selects chitosan from discarded shrimp shells and crab shells as the main raw material, so that the guided bone regeneration membrane has good biocompatibility and biodegradability, and reduces the cost. Phosphate and calcium salt are doped to effectively mimic the natural bone tissue structure. With the rich functional groups (amino groups) of chitosan, the oriented crystallization and uniform dispersion of nanohydroxyapatite are induced in situ, thereby enhancing the bone mineralization ability by nanomechanics. The mechanical extrusion method is used to prepare a dense composite double-layer structure, the preparation process is simple, and large-scale production can be achieved. It is expected to become a new type of guided bone regeneration membrane to play its unique role in the repair of tooth bone defects. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of the existing guided bone regeneration membrane being expensive, lacking in bone mineralization ability, and having poor therapeutic effect. Chitosan derived from shrimp and crab shells is used as an organic matrix, calcium nitrate is used as a calcium source, and dipotassium hydrogen phosphate is used as a phosphate salt. A freeze-drying technology is combined with a mechanical extrusion method to provide a preparation method for a chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure. The preparation process is simple, the cost is low, and the nano-dispersion and bone mineralization effect are good.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: Using the technology and methods of material preparation, a chitosan / nanohydroxyapatite guided bone regeneration membrane with good biocompatibility, biodegradability and sparse-dense composite structure was designed for the repair of tooth bone defects. Chitosan was used as the organic matrix, and calcium salts and phosphates were uniformly mineralized and crystallized on the surface of chitosan polymer chains by freeze-drying in situ to form nanohydroxyapatite, and nanomechanics enhanced the bone mineralization ability. Through a simple mechanical extrusion method, it has a sparse-dense asymmetric double-layer structure. This is because one side of the membrane contacts the smooth mechanical surface, and all the original pores are compacted into a dense layer, while the other side of the membrane contacts the polytetrafluoroethylene mold with a grid, and most of the original pores are preserved during the extrusion process. Its dense layer mainly plays a shielding role, which can effectively prevent faster-growing tissue cells from entering the root (bone) defect area and provide sufficient bone formation space for the defect area; the loose porous layer can guide the recruitment of periodontal ligament (or bone) cells and provide them with growth space, forming a microenvironment conducive to tissue regeneration. In this way, a chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure is prepared. Specifically, the following steps are included: (1) Prepare acetic acid solution, dissolve an appropriate amount of chitosan in the weak acid solution, and stir in a water bath to mix well to obtain chitosan acetic acid solution.
[0006] (2) Add calcium nitrate solution to the chitosan acetic acid solution, continue stirring until uniform, then add an appropriate amount of dipotassium hydrogen phosphate solution, continue stirring for a period of time to obtain a guided bone regeneration membrane precursor solution.
[0007] (3) The precursor solution of the guided bone regeneration membrane is transferred to a refrigerator for pre-freezing, freeze-dried in a freeze dryer for several hours, and then immersed in an ethanol / deionized water solution of sodium hydroxide to achieve in situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0008] (4) Rinse repeatedly with deionized water until neutral, transfer to a refrigerator for pre-freezing, and then freeze-dry for several hours using a freeze dryer.
[0009] (5) After freeze-drying, the membrane is placed on the mesh surface of a polytetrafluoroethylene mold with a mesh and squeezed for several hours under a certain mechanical strength to obtain a chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
[0010] Furthermore, in the chitosan acetic acid solution of step (1), the amount of acetic acid is 0.5 mL, the amount of water is 49.5 mL, and the mass of chitosan powder is 1 g.
[0011] Furthermore, in step (2), the concentration of the calcium nitrate solution is 2 mol / L, and the amount used is 2 mL. The concentration of the dipotassium hydrogen phosphate solution is 1.2 mol / L, and the amount used is 2 mL.
[0012] Furthermore, in step (3), the pre-freezing method is to place at 4°C for 1 hour and at -80°C for 24 hours.
[0013] Furthermore, in the ethanol / deionized water solution of sodium hydroxide in step (3), the mass of sodium hydroxide is 1 g, the amount of ethanol is 125 mL, the amount of deionized water is 125 mL, and the soaking time is 10 h.
[0014] Furthermore, in step (4), the pre-freezing method is to directly transfer to -80°C for storage.
[0015] Furthermore, in step (5), the strength used for mechanical extrusion is 0.2 MPa to 5 MPa.
[0016] Furthermore, in step (5), the mechanical extrusion time is 12 hours to 96 hours.
[0017] Furthermore, in step (5), during mechanical extrusion, one side of the membrane contacts a smooth mechanical surface, and the pores are compacted into a dense layer, while the other side of the membrane contacts a polytetrafluoroethylene mold with a grid, which preserves the original pores during the extrusion process while also making the surface looser.
[0018] A chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure prepared by the above method.
[0019] The significant advantages of the present invention are: (1) The present invention utilizes the rich functional groups (amino groups) of chitosan to in-situ induce the oriented crystallization and uniform dispersion of nano-hydroxyapatite, thereby enhancing the bone mineralization ability through nanomechanics.
[0020] (2) The guided bone regeneration membrane prepared by the present invention has a dense and sparse composite double-layer structure. The dense layer can effectively prevent fast-growing tissue cells from entering the root (bone) defect area, and the loose porous layer can guide the recruitment of periodontal ligament (or bone) cells and provide them with growth space, ensuring the best tissue regeneration effect.
[0021] (3) The present invention uses a mechanical extrusion method, which has low preparation cost, simple method, green and environmental protection, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The structural diagram of the polytetrafluoroethylene mold with a grid; (a) top view of the mold, (b) side view of the mold; Figure 2 Surface morphology photos of Examples 1-5, wherein S-1 to S-5 correspond to Examples 1 to 5, respectively; Figure 3This is a depth of field electron microscope image of the double-sided dense chitosan / nanohydroxyapatite guided bone regeneration membrane prepared in Example 1; Figure 4 Scanning electron microscope images of the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure prepared in Example 2-5; (a) loose porous surface, (b) dense surface, (c) cross section; Figure 5 Determination of water absorption of guided bone regeneration membranes prepared in Examples 1-5; Figure 6 This is a biocompatibility test of the guided bone regeneration membrane prepared in Example 5 (n=4, *p<0.05, **p<0.01, ***p<0.001). DETAILED DESCRIPTION
[0023] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further explained below in combination with specific implementation methods. However, the following examples are merely examples of the present invention and do not represent the scope of protection of the rights limited by the present invention. The scope of protection of the present invention shall be subject to the claims.
[0024] Example 1 (1) Prepare 50 mL of 1% (V / V) acetic acid solution, accurately weigh 1 g of chitosan and dissolve it in this weak acid solution, and stir in a water bath at 60°C for 4 h to mix it evenly.
[0025] (2) Add 2 mL of 2 mol / L calcium nitrate solution to the chitosan acetic acid solution and continue stirring for 2 h. Then add 2 mL of 1.2 mol / L potassium dihydrogen phosphate solution and continue stirring for 4 h to obtain a guided bone regeneration membrane precursor solution.
[0026] (3) Transfer to refrigerator for pre-freezing: place at 4℃ for 1 hour, and place at -80℃ for 24 hours. Freeze-dry at -80℃ for 48 hours. Then place in ethanol / deionized water solution of sodium hydroxide (sodium hydroxide mass is 1 g, ethanol amount is 125 mL, deionized water amount is 125 mL) and soak for 10 hours to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0027] (4) Wash repeatedly with deionized water until neutral. Transfer to a refrigerator and pre-freeze at -80°C for 24 hours, then freeze-dry at -80°C for 48 hours using a freeze dryer.
[0028] (5) After freeze-drying, the membrane was extruded at a mechanical strength of 0.66 MPa for 24 h to obtain a chitosan / nanohydroxyapatite guided bone regeneration membrane with dense surfaces on both sides.
[0029] Example 2 (1) Prepare 50 mL of 1% (V / V) acetic acid solution, accurately weigh 1 g of chitosan and dissolve it in this weak acid solution, and stir in a water bath at 60°C for 4 h to mix it evenly.
[0030] (2) Add 2 mL of 2 mol / L calcium nitrate solution to the chitosan acetic acid solution and continue stirring for 2 h. Then add 2 mL of 1.2 mol / L potassium dihydrogen phosphate solution and continue stirring for 4 h to obtain a guided bone regeneration membrane precursor solution.
[0031] (3) Transfer to refrigerator for pre-freezing: place at 4℃ for 1 hour, and place at -80℃ for 24 hours. Freeze-dry at -80℃ for 48 hours. Then place in ethanol / deionized water solution of sodium hydroxide (sodium hydroxide mass is 1 g, ethanol amount is 125 mL, deionized water amount is 125 mL) and soak for 10 hours to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0032] (4) Wash repeatedly with deionized water until neutral. Transfer to a refrigerator and pre-freeze at -80°C for 24 hours, then freeze-dry at -80°C for 48 hours using a freeze dryer.
[0033] (5) After freeze-drying, the mixture was placed on a mesh surface of a polytetrafluoroethylene mold with a 16-mesh mesh and extruded at a mechanical strength of 0.66 MPa for 24 hours to obtain the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
[0034] Example 3 (1) Prepare 50 mL of 1% (V / V) acetic acid solution, accurately weigh 1 g of chitosan and dissolve it in this weak acid solution, and stir in a water bath at 60°C for 4 h to mix it evenly.
[0035] (2) Add 2 mL of 2 mol / L calcium nitrate solution to the chitosan acetic acid solution and continue stirring for 2 h. Then, add 2 mL of 1.2 mol / L potassium dihydrogen phosphate solution and continue stirring for 4 h to obtain a guided bone regeneration membrane precursor solution.
[0036] (3) Transfer to refrigerator for pre-freezing: place at 4℃ for 1 hour, and place at -80℃ for 24 hours. Freeze-dry at -80℃ for 48 hours. Then place in ethanol / deionized water solution of sodium hydroxide (sodium hydroxide mass is 1 g, ethanol amount is 125 mL, deionized water amount is 125 mL) and soak for 10 hours to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0037] (4) Wash repeatedly with deionized water until neutral. Transfer to a refrigerator and pre-freeze at -80°C for 24 hours, then freeze-dry at -80°C for 48 hours using a freeze dryer.
[0038] (5) After freeze-drying, the mixture was placed on a mesh surface of a polytetrafluoroethylene mold with a 16-mesh mesh and extruded for 48 hours at a mechanical strength of 0.66 MPa to obtain the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
[0039] Example 4 (1) Prepare 50 mL of 1% (V / V) acetic acid solution, accurately weigh 1 g of chitosan and dissolve it in this weak acid solution, and stir in a water bath at 60°C for 4 h to mix it evenly.
[0040] (2) Add 2 mL of 2 mol / L calcium nitrate solution to the chitosan acetic acid solution and continue stirring for 2 h. Then, add 2 mL of 1.2 mol / L potassium dihydrogen phosphate solution and continue stirring for 4 h to obtain a guided bone regeneration membrane precursor solution.
[0041] (3) Transfer to refrigerator for pre-freezing: place at 4℃ for 1 hour, and place at -80℃ for 24 hours. Freeze-dry at -80℃ for 48 hours. Then place in ethanol / deionized water solution of sodium hydroxide (sodium hydroxide mass is 1 g, ethanol amount is 125 mL, deionized water amount is 125 mL) and soak for 10 hours to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0042] (4) Wash repeatedly with deionized water until neutral. Transfer to a refrigerator and pre-freeze at -80°C for 24 hours, then freeze-dry at -80°C for 48 hours.
[0043] (5) After freeze-drying, the mixture was placed on a mesh surface of a polytetrafluoroethylene mold with a 16-mesh mesh and extruded at a mechanical strength of 0.88 MPa for 24 hours to obtain the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
[0044] Example 5 (1) Prepare 50 mL of 1% (V / V) acetic acid solution, accurately weigh 1 g of chitosan and dissolve it in this weak acid solution, and stir in a water bath at 60°C for 4 h to mix it evenly.
[0045] (2) Add 2 mL of 2 mol / L calcium nitrate solution to the chitosan acetic acid solution and continue stirring for 2 h. Then, add 2 mL of 1.2 mol / L potassium dihydrogen phosphate solution and continue stirring for 4 h to obtain a guided bone regeneration membrane precursor solution.
[0046] (3) Transfer to refrigerator for pre-freezing: place at 4℃ for 1 hour, and place at -80℃ for 24 hours. Freeze-dry at -80℃ for 48 hours. Then place in ethanol / deionized water solution of sodium hydroxide (sodium hydroxide mass is 1 g, ethanol amount is 125 mL, deionized water amount is 125 mL) and soak for 10 hours to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite.
[0047] (4) Wash repeatedly with deionized water until neutral. Transfer to a refrigerator and pre-freeze at -80°C for 24 hours, then freeze-dry at -80°C for 48 hours using a freeze dryer.
[0048] (5) After freeze-drying, the mixture was placed on a mesh surface of a polytetrafluoroethylene mold with a 16-mesh mesh and extruded at a mechanical strength of 0.88 MPa for 48 hours to obtain the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
[0049] The polytetrafluoroethylene mold with 16-mesh raised grid used in Examples 2-5 is shown in FIG. Figure 1 , (a) is a top view of the mold, and (b) is a side view of the mold. The rectangular protrusions (1mm*1mm*0.3mm) on the top of the mold form a grid structure of the mold, and the gaps between the protrusions can effectively retain most of the original loose structure of the guided bone regeneration membrane.
[0050] The morphology of the guided bone regeneration membrane prepared in Example 1-5 is shown in Figure 2 .
[0051] The depth of field electron microscope image of the guided bone regeneration membrane prepared in Example 1 is shown in Figure 3 .
[0052] The SEM images of the guided bone regeneration membrane prepared in Example 2-5 are shown in Figure 4 .
[0053] The water absorption of the guided bone regeneration membrane prepared in Example 1-5 is shown in Figure 5 .
[0054] The biocompatibility test of the guided bone regeneration membrane prepared in this Example 5 is shown in Figure 6 .
[0055] The morphology of guided bone regeneration membrane ( Figure 2 ) It can be seen that the guided bone regeneration membrane prepared in the experiment is a round cake-shaped membrane with a diameter of about 1.2 cm and a thickness of about 0.5-1.2 mm, one side is loose and the other side is dense. The guided bone regeneration membrane after freeze-drying is white in color. With the extension of pressing time and the increase of pressing pressure, the thickness of the membrane gradually decreases. Observation found that there was no obvious difference in the periosteum surface of the five groups.
[0056] Through the depth of field electron microscopy ( Figure 3), the guided bone regeneration membrane prepared in Example 1 presents a structure with compacted pores.
[0057] Through SEM, the four groups of guided bone regeneration membranes showed obvious different structures ( Figure 4 ). Its loose surface presents a porous structure (a), and the dense surface presents a structure with compacted pores (b). And as the pressing time increases and the pressing pressure increases, the pore characteristics of the loose surface of the membrane become less obvious, and the dense surface becomes more dense. This change also conforms to the characteristics of the mechanical extrusion method of the present invention.
[0058] Having appropriate water absorption capacity helps the periosteum maintain a moist environment at the tissue defect site and provides a favorable external environment for cell growth and reproduction. Figure 5 The results of the water absorption analysis of the periosteum show that all five groups of periosteum materials have high water absorption, and the water absorption rate can reach more than 300% (S-1: 361%, S-2: 758%, S-3: 485%, S-4: 719%, S-5: 456%). Such a high water absorption rate is sufficient to maintain the dynamic balance of nutrients and active factors in the microenvironment of the defect site, and provide protection for the material transport and metabolism of the new tissue. Among them, the water absorption of S-2, S-3, S-4, and S-5 is greater than that of S-1, mainly due to the porous structure of the loose surface. As the pressing time increases and the pressing pressure increases, the water absorption of the membrane gradually decreases, mainly because the pore characteristics of the loose surface of the membrane become less obvious, and this change is also in line with the characteristics of the mechanical extrusion method of the present invention.
[0059] CCK-8 reagent can quickly test the effect of periosteum on the proliferation of MC3T3-E1 cells. The OD value of the culture plate at 450nm can be measured by an enzyme-labeled instrument and then calculated according to the formula to intuitively display the cell number and viability. Figure 6 As shown. Figure 6 It can be seen that with the extension of culture time, the number of cells showed an increasing trend. At 1 day of co-culture, the number of cell proliferation in the experimental group was slightly lower than that in the blank group. On the 3rd and 5th days, it can be seen that the number of cell proliferation was significant. Compared with the blank group, the cell activity in the experimental group was higher, and the experimental results were significantly different, which was due to the fact that the chitosan / nanohydroxyapatite system could promote cell proliferation. It shows that chitosan / nanohydroxyapatite has good biocompatibility and is non-toxic to cells. Therefore, the experimental results show that chitosan / nanohydroxyapatite guided bone regeneration membrane has excellent biocompatibility and helps promote the adhesion and proliferation of MC3T3-E1 cells.
[0060] Water absorption determination: Weigh the dried guided bone regeneration membranes of different groups and record their weight as W1. Then put them into 50mL centrifuge tubes with 30mL distilled water. After marking, place each group of centrifuge tubes in a constant temperature shaker at 37℃ and 150 r / min. Take out the samples after 24h. The excess water on the surface is absorbed with filter paper and weighed, and its mass is recorded as W2. Repeat three times for each sample. The water absorption (A) of the prepared guided bone regeneration membrane is calculated as follows.
[0061] A(%)=(W2-W1) / W1*100% W2 in the formula represents the weight of the bracket after absorbing water, and W1 represents the mass of the bracket before absorbing water.
[0062] Biocompatibility testing: The biocompatibility of the guided bone regeneration membrane was detected using the CCK-8 kit. The MC3T3-E1 cells with good cell growth were resuspended and counted, and the cell concentration was calculated. Then, the cells were inoculated in a sterile 96-well plate at a cell density of 5000 per well, and then an appropriate amount of complete culture medium was added to ensure that the volume of the liquid in each well was 100 μL. Five parallel wells were set up in each group, and the complete culture medium was replaced every two days. The cells were stained using the CCK-8 kit on the 1st, 3rd and 5th days of culture. The operation process was carried out according to the instructions of the CCK-8 kit (Shanghai Bioengineering), and the absorbance value at 450 nm was detected by an ELISA instrument. Note that in this process, the wells containing no cells and only CCK-8 detection solution were used as blank wells for deducting background values, DMEM / F-12 complete cell culture medium was used as a blank control group, and the guided bone regeneration membrane extract group of Example 5 was used to culture cells in the experimental group. The calculation formula for cell survival rate (S) is as follows: S(%)=(Os-Ob / Oc-Ob)*100% Wherein Os in the formula represents the absorbance value in the experimental group, Oc represents the absorbance value in the blank control group, and Ob represents the absorbance value of the blank well containing only CCK-8 detection solution.
[0063] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure, characterized in that: Chitosan was used as the organic matrix, and freeze-drying was used to in situ induce the uniform mineralization and crystallization of calcium salts and phosphates on the surface of chitosan polymer chains to form nano-hydroxyapatite. Combined with mechanical extrusion, a chitosan / nano-hydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure was prepared.
2. The method for preparing the chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure according to claim 1, characterized in that: The following steps are involved: (1) preparing an acetic acid solution, dissolving an appropriate amount of chitosan in the acetic acid solution, and stirring in a water bath to obtain a chitosan acetic acid solution; (2) Adding calcium nitrate solution to the chitosan acetic acid solution, stirring continuously until uniform, then adding an appropriate amount of dipotassium hydrogen phosphate solution, stirring continuously for a period of time to obtain a precursor solution of guided bone regeneration membrane; (3) The precursor solution of the guided bone regeneration membrane is transferred to a refrigerator for pre-freezing, freeze-dried in a freeze dryer for several hours, and then immersed in an ethanol / deionized water solution of sodium hydroxide to achieve in-situ mineralization and crystallization on the surface of chitosan to achieve uniform distribution of nano-hydroxyapatite; (4) Repeatedly rinse with deionized water until neutral, transfer to a refrigerator for pre-freezing, and then freeze-dry for several hours using a freeze dryer; (5) After freeze-drying, the membrane is placed on the mesh surface of a polytetrafluoroethylene mold with a mesh and squeezed for several hours under a certain mechanical strength to obtain a chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure.
3. The preparation method according to claim 2, characterized in that: In the chitosan acetic acid solution of step (1), the amount of acetic acid is 0.5 mL, the amount of water is 49.5 mL, and the mass of chitosan powder is 1 g.
4. The preparation method according to claim 2, characterized in that: In step (2), the concentration of the calcium nitrate solution is 2 mol / L, and the amount used is 2 mL; the concentration of the dipotassium hydrogen phosphate solution is 1.2 mol / L, and the amount used is 2 mL.
5. The preparation method according to claim 2, characterized in that: In step (3), the pre-freezing method is to place it at 4°C for 1 hour and at -80°C for 24 hours.
6. The preparation method according to claim 2, characterized in that: In the ethanol / deionized water solution of sodium hydroxide in step (3), the mass of sodium hydroxide is 1 g, the amount of ethanol is 125 mL, and the amount of deionized water is 125 mL; the soaking time is 10 h.
7. The preparation method according to claim 2, characterized in that: In step (4), the pre-freezing method is to directly transfer to -80°C for storage.
8. The preparation method according to claim 2, characterized in that: In step (5), the intensity used for mechanical extrusion is 0.2 MPa to 5 MPa; and the mechanical extrusion time is 12 h to 96 h.
9. The preparation method according to claim 2, characterized in that: In step (5), during mechanical extrusion, one side of the membrane contacts a smooth mechanical surface, and the pores are compacted into a dense layer, while the other side of the membrane contacts a polytetrafluoroethylene mold with a grid, which preserves the original pores during the extrusion process while making the surface looser.
10. The chitosan / nanohydroxyapatite guided bone regeneration membrane with a sparse-dense composite structure obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Guided tissue regeneration membrane and its preparation method
CN102716517A
Nano-hydroxyapatite / chitosan / chondroitin sulfuric acid composite stent
CN102921045A
Double-layer composite regeneration film and making method thereof
CN103191085A
Composite material of organic / inorganic multi-phase induction nano-hydroxyapatite
CN106075590A
Bioremediation membrane and preparation method thereof
CN117018292A
Cited By
Double-layer guided bone regeneration membrane and preparation method thereof
CN121754741A
